An Air‐Stable Molybdenum‐Based Precatalyst in Oxygen‐Atom Transfer Reactions. Issue 12 (30th March 2018) - Oheix, Emmanuel; Orio, Maylis; Giorgi, Michel; Réglier, Marius; Iranzo, Olga; Hardré, Renaud Y.
Abstract : We report on the preparation and characterization of two new air‐stable mononuclear molybdenum(VI) complexes, termed Mo VI O2 (OPNO)2 (1 ) and Mo VI O2 (SPNO)2 (2 ). The potential of these complexes to act as functional mimics of molybdoenzymes from the DMSO reductase family was investigated. Initial catalytic studies suggest that2 (but not1 ) catalyzes the reduction of a sulfoxide into the thioether derivative. Studying the catalytic intermediates by UV/Vis spectroscopy, NMR spectroscopy, and DFT indicates that the active species (SPNO)2 OMo V –O–Mo V O(SPNO)2 (4 ), a dinuclear molybdenum(V) dimer with one µ‐oxo bridge, is formed upon successive reduction of the (SPNO) – ligands and the molybdenum(VI) ion. Abstract : Two new complexes of bis‐oxo‐molybdenum have been prepared and investigated in oxygen transfer reactions. Mo(OPNO)2 O2 is inactive in this reaction under our conditions. In contrast, Mo(SPNO)2 O2 can act as a (pre)catalyst in this reaction. On the basis of the combined theoretical and spectroscopic results, a mechanism is proposed involving a µ‐oxo Mo V dimer.